2018
DOI: 10.3390/s18020605
|View full text |Cite
|
Sign up to set email alerts
|

UAVs and Machine Learning Revolutionising Invasive Grass and Vegetation Surveys in Remote Arid Lands

Abstract: The monitoring of invasive grasses and vegetation in remote areas is challenging, costly, and on the ground sometimes dangerous. Satellite and manned aircraft surveys can assist but their use may be limited due to the ground sampling resolution or cloud cover. Straightforward and accurate surveillance methods are needed to quantify rates of grass invasion, offer appropriate vegetation tracking reports, and apply optimal control methods. This paper presents a pipeline process to detect and generate a pixel-wise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 27 publications
1
26
0
1
Order By: Relevance
“…For the RF and XGB, molecular descriptors were calculated using a Python package called Mordred () [64]. Classification experiments were conducted in the Python programming language using specific classifier implementations, RF, and XGB provided by the scikit-learn and rdkit Python packages [76,77,78,79].…”
Section: Methodsmentioning
confidence: 99%
“…For the RF and XGB, molecular descriptors were calculated using a Python package called Mordred () [64]. Classification experiments were conducted in the Python programming language using specific classifier implementations, RF, and XGB provided by the scikit-learn and rdkit Python packages [76,77,78,79].…”
Section: Methodsmentioning
confidence: 99%
“…Examples of invasive species detected through the use of drones in combination with image processing include: yellow flag iris (Iris pseudacorus; Baron et al 2018), invasive grasses (Cenchrus ciliaris and Triodia spp. ; Sandino et al 2018), Burmese pythons (Python bivittatus; Gomes 2017), and silk oak trees (Grevillea robusta; Strohecker 2017).…”
Section: Unmanned Aerial Vehicles and Remotely Operated Vehiclesmentioning
confidence: 99%
“…For example, researchers at the University of Alberta used machine learning to analyze the factors that led to success or failure in 143 attempts to eradicate aquatic invasive species and developed a decision tree for responders in the field to guide their choice of response strategy (Xiao et al 2018). Campbell et al (2015) predict that drones, in combination with infrared cameras, preprogrammed night flights, bait delivery mechanisms, and AI data processing, will be widely adopted for invasive rodent eradication programs within the next five years (see also Sandino et al 2018). Below we provide a brief overview of response tools not previously discussed in this paper.…”
Section: Response Technologiesmentioning
confidence: 99%
“…We found that the use of the non-destructive SfM method accurately estimated AGB in plots of mixed grasses, including annual and perennial, and forbs in low elevation sagebrush steppe ecosystems. Often a spectral classification is used to discriminate between PFT's or vegetation species before analysis (Akar et al, 2017;Gaston et al, 2018;Jing et al, 2017;Lu & He, 2017). Spectral data from images in this study were not used because they were not radiometrically corrected.…”
Section: Discussionmentioning
confidence: 99%
“…If available, more training data for sparse classes will improve the accuracy in the classification. The advent of unmanned aerial vehicles (UAVs) allows for field data collection of a large area in less time compared to a field crew (Gaston et al, 2018). UAV flights could be instrumental for collecting test and training data for landscape scale observations and provide imagery to develop a more accurate percent cover of vegetation for individual pixels (Breckenridge et al, 2012).…”
Section: Table 25 Confusion Matrix For the Vegetation Classificationmentioning
confidence: 99%